Modul Mata Pelajaran Sejarah Menengah Rendah Berasaskan Pembelajaran Mudah Alih: Satu Kajian Delphi - Zulkifli, Mohd Hafiz Shafiq (2023)
The digitization process today has opened up new dimensions in various fields to shift the use of mobile technology, including in education. This study explores the potential of using mobile learning to be integrated into Malaysia's lower secondary History subjects. Therefore, the theoretical model approach of Technological Pedagogical Content Knowledge (TPACK) is used in this study to explore the potential of the components to integrate with History teaching lessons. Based on the components of Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), and Technological Pedagogical Knowledge (TPK), a draft module content has been designed based on the results of a needs analysis of over 30 History teachers at the lower secondary school level. The Visual, Aural, Reading, and Kinesthetic based on VARK model was used in the study to adapt according to the tendency of each history learning content with the delivery of teaching content using mobile technology through the integration of PCK components. The study also used the modified Delphi method for two rounds to obtain verification and consensus on the draft module content. Experts from instructional technology and history education were selected (n=6) by dividing them into each round.